Clinical, histopathological and immunohistochemical analysis of vulvar squamous cell carcinoma - Lorenza Bridi Todeschini; Rita de Cássia Sant’Anna Alves; Adriana Vial Roehe (Revista Brasileira de Ginecologia e Obstetrícia)
Abstract Objective: The average age of patients with vulvar squamous cell carcinoma (SCC) has been reported to have declined. Human papilloma virus (HPV)-related lesions have been shown to be associated with the expression of the immunohistochemical (IHC) marker p16. Non-HPV-related tumors have been characterized by p53 abnormal expression and PDL1 expression. We aimed to evaluate the correlation between these markers and vulvar SCC and to relate it to the clinical and pathological characteristics. Methods: Histopathologic assessments and IHC analyses of p16, p53, and PDL1 were performed in 41 samples of vulvar SCC collected between 2016 and 2021. The data were correlated with clinical and pathological characteristics of the patients. Results: The mean age of the patients was 72.1 years. Positive p16 and PDL1 staining was detected in 24.4% and 17.1% of the samples, respectively. p53 expression was negative in 19.5% of the samples, whereas it was overexpressed in 24.4%. p16-positive tumors showed a smaller depth of invasion (DOI) (p = 0.014), while tumors with p53 abnormal expression showed greater DOI (p = 0.041). PDL1 expression was correlated with increased number of inflammatory cells (p = 0.055). In addition, lesions with lymphovascular space invasion were p16-negative. Conclusion: In our sample, regarding to the SCC incidence the patients’ mean age did not change. The expression of p16 was inversely correlated with p53 results. Tumors with p53 abnormal expression and absence of p16 showed a greater DOI. Our data suggest an association between PDL1 expression and increased inflammatory infiltrates in vulvar SCC.